Three Approaches to Strategy human resource management based on management - Sugiyono Sugiyono (Greenation International Journal of Economics and Accounting, 2023)
This paper as an importanHuman Resource Management (HRM) in enhancement processes of knowledge managemen. Every company should be able to see the existing challenges and potential in its human resources. Good human resource governance will improve the quality of cooperation among employees of the company. Moreover, effective human resource governance encourages creativity in every problem-solving process. Creativity and work efficiency of human resources can improve the overall organizational performance. The fundamental aim of strategic human resources management is to generate strategic capability by ensuring that the organization has the skilled, committed and well-motivated employees it needs to achieve sustained competitive advantage.